Do foreign-educated nurses displace native-educated nurses? - Hyeran Chung; Mary Arends-Kuenning (IZA Journal of Labor Policy, 2020)
We examine whether there is any movement in the employment of native-educated nurses due to the influx of foreign-educated nurses. To avoid conflating the short- and long-term reactions to the entry of newly arrived foreign-educated nurses, we implement a multiple instrumentation procedure. We find that there is no significant effect of foreign-educated nurses on the employment of native nurses in both the short- and the long-runs. Our results suggest that relying on foreign-educated nurses to fill gaps in the US healthcare workforce does not harm the employment of native nurses.
Keywords: J11; J44; J61; 330; foreign-educated nurses; immigration; displacement; a double instrumentation procedure